Pengembangan Objek Wisata Pantai Impos Desa Medana Terhadap Peningkatan Pendapatan Pedagang - Nazwa Indira Ramadhanti; Lalu Hendra Maniza; Muhammad Aprian Jailani; Baiq Reinelda Tri Yunarni (CV. ITTC INDONESIA, 2025)
Tourism is one of the sectors that is a top priority in regional development by the government. The development of the right tourist attraction affects the increase in the number of visitors and encourages the economic income of traders. The development of Impos Beach tourist attraction is expected to increase the number of visitors and directly increase the income of traders. This study aims to analyze how the development of Impos Beach tourist attraction by pokdarwis towards increasing the income of traders and to analyze what factors and obstacles experienced during the development of Impos Beach tourist attraction Medana Village. The method used in this research is a descriptive qualitative approach and data collection techniques using observation, interviews, and documentation. The results of this study indicate that the development carried out by the Pokdarwis on the Impos Beach tourist attraction directly affects the increase in the number of tourists and the income of traders will also increase, which previously ranged from Rp. 150,000 - Rp. 200,000 per day and after ranging from Rp. 1,000,000 - Rp. 1,500,000, in other words, development not only attracts more tourists, but also contributes to increasing trader income, so that the two are interrelated between the development of tourist attractions and increasing trader income. The results of this study also show that the supporting factors during the development were the role of the village government which provided budget funds at the time of the opening of Impos Beach and the role of the Pokdarwis Sejahtera Impos Beach which managed and developed tourism potential, making management more effective and attracting more tourists who came while the obstacles experienced such as, lack of cohesiveness between Pokdarwis members, lack of awareness from visitors related to hygiene issues, especially garbage, assistance that has not been optimal from the Government, and limited support from the North Lombok Regency Tourism Office.